Reisaction - Réseau de l’est de l’île pour les services en anglais (REISA) (2019)
Number of pages: 5

Annual Report : 2018-2019 - Réseau de l’est de l’île pour les services en anglais (REISA) (2019)

Employability Initiatives : 2019-2021 - Réseau de l’est de l’île pour les services en anglais (REISA) (2019)

Health and Social Service Resources for English-Speaking Communities in the East and North of Montreal : 2019-2020 - Réseau de l’est de l’île pour les services en anglais (REISA) (2019)

Health and Social Service Resources for the English-speaking Seniors in the East end of Montreal - Réseau de l’est de l’île pour les services en anglais (REISA) (2019)

Reisaction - Réseau de l’est de l’île pour les services en anglais (REISA) (2018)
Number of pages: 3

Resources for Families with Special Needs - Réseau de l’est de l’île pour les services en anglais (REISA) (2018)

Annual Report : 2017-2018 - Réseau de l’est de l’île pour les services en anglais (REISA) (2018)

Health and Social Service Resources for English-Speaking Communities in the East and North of Montreal : 2018 - Réseau de l’est de l’île pour les services en anglais (REISA) (2018)

Health and Social Service Resources for the English-speaking Seniors in the East end of Montreal - Réseau de l’est de l’île pour les services en anglais (REISA) (2018)

Reisaction Newsletter - Réseau de l’est de l’île pour les services en anglais (REISA) (2018)
Number of pages: 7

Resources for Families with Special Needs - Réseau de l’est de l’île pour les services en anglais (REISA) (2017)

Reisaction Newsletter - Réseau de l’est de l’île pour les services en anglais (REISA) (2017)
Number of pages: 10

Reisaction Newsletter - Réseau de l’est de l’île pour les services en anglais (REISA) (2017)
Number of pages: 4

The Network Model : Influencing Public Policy for Social Change - Community Health and Social Services Network (CHSSN) (2017)
The case studies being presented in today demonstrate that the development principles are at work every day and are now being pressed into new areas of action. The values underpinning the network model include promoting the identity of our communities, promoting social inclusion and advocating for equity in the broader society in its treatment of communities. These values can support network strategies to enter the “next level” of participation in societal initiatives setting broad policy goals. The reward for such effort can be societal recognition that the programs that define Quebec’s commitment to social progress also include our communities.

Reisaction Newsletter - Réseau de l’est de l’île pour les services en anglais (REISA) (2017)
Number of pages: 2

Annual Report : 2016-2017 - Réseau de l’est de l’île pour les services en anglais (REISA) (2017)

Health and Social Service Resources for English-Speaking Communities in the East and North of Montreal : 2017 - Réseau de l’est de l’île pour les services en anglais (REISA) (2017)

Health and Social Service Resources for the English-speaking Seniors in the East end of Montreal - Réseau de l’est de l’île pour les services en anglais (REISA) (2017)

Reisaction Newsletter - Réseau de l’est de l’île pour les services en anglais (REISA) (2017)
Number of pages: 8

Reisaction Newsletter - Réseau de l’est de l’île pour les services en anglais (REISA) (2017)
Number of pages: 7

Report : Community Network Forum - Community Health and Social Services Network (CHSSN) (2016)
Health promotion is an activity that community organizations can adopt to enhance visibility and credibility in their communities. Health promotion activities can respond to real needs of different groups and create opportunities to engage the public system with the community organization and the constituencies it serves. For the public network, a community organization that has established a health promotion role has the potential to become a prime partner in helping an institution better serve its target population. In recent years, community networks have developed health promotion programs that have reached thousands of community members and can now demonstrate positive results. The Forum will discuss how this development is resulting in promising and best practices, and inspiring a range of public and community interests to engage in health promotion for English-speaking communities.

Ahuntsic Cartierville : English-speaking Population 2016 / Ahuntsic Cartierville : Population d'expression anglaise 2016 - Réseau de l’est de l’île pour les services en anglais (REISA) (2016)

Anjou : English-speaking Population 2016 / Anjou : Population d'expression anglaise 2016 - Réseau de l’est de l’île pour les services en anglais (REISA) (2016)

Annual Report : 2015-2016 - Réseau de l’est de l’île pour les services en anglais (REISA) (2016)

East-Island Network Newsletter : Reisaction - Réseau de l’est de l’île pour les services en anglais (REISA) (2016)
Number of pages: 4

McGill Retention of Health Professionals Project : Community Organization Descriptions 2015 - 2016 - Réseau de l’est de l’île pour les services en anglais (REISA) (2016)

Mercier Hochelaga-Maisonnneuve : English-speaking Population 2016 / Mercier Hochelaga-Maisonnneuve : Population d'expression anglaise 2016 - Réseau de l’est de l’île pour les services en anglais (REISA) (2016)

Montréal-Nord : English-speaking Population 2016 / Montréal-Nord : Population d'expression anglaise 2016 - Réseau de l’est de l’île pour les services en anglais (REISA) (2016)

Rivière-des-Prairies and Pointe-aux-Trembles : English-speaking Population 2016 / Rivière-des-Prairies and Pointe-aux-Trembles : Population d'expression anglaise 2016 - Réseau de l’est de l’île pour les services en anglais (REISA) (2016)

Rosemont La Petite-Patrie l'Est : English-speaking Population 2016 / Rosemont-La Petite-Patrie-l-est : Population d'expression anglaise 2016 - Réseau de l’est de l’île pour les services en anglais (REISA) (2016)

Rosemont La Petite-Patrie Nord : English-speaking Population 2016 / Rosemont La Petite-Patrie Nord : Population d'expression anglaise 2016 - Réseau de l’est de l’île pour les services en anglais (REISA) (2016)

Saint-Laurent : English-speaking Population 2016 / Saint-Laurent : Population d'expression anglaise 2016 - Réseau de l’est de l’île pour les services en anglais (REISA) (2016)

Saint-Léonard : English-speaking Population 2016 / Saint-Léonard : Population d'expression anglaise 2016 - Réseau de l’est de l’île pour les services en anglais (REISA) (2016)

Villeray–Saint-Michel–Parc-Extension : English-speaking Population 2016 / Villeray–Saint-Michel–Parc-Extension : Population d'expression anglaise 2016 - Réseau de l’est de l’île pour les services en anglais (REISA) (2016)

The East Island Retention of Health Professionals Project – English, An Asset! : REISA Internships - A Success Story - Gatre Guemiri, Fatiha; Zappitelli, Juliana; Mirtaheri, Mina; Granner, Francine; Hendrickson-Nelson, Mary (2015)

Report : Community Network Forum - Community Health and Social Services Network (CHSSN) (2015)
Community organizations carry out their missions in an environment of continual reorganization of the health and social services system. In this context, groups must face the challenge of mobilizing resources to engage communities in a collective effort to commit the public system to meet the specific needs of community members. Groups are also challenged to introduce innovative approaches into their programs in a continual effort to achieve positive and long-lasting results.

Annual Report : 2014-2015 - Réseau de l’est de l’île pour les services en anglais (REISA) (2015)

Community in Movement Forum - Réseau de l’est de l’île pour les services en anglais (REISA) (2014)

Annual Report : 2013-2014 - Réseau de l’est de l’île pour les services en anglais (REISA) (2014)

East-Island Network Newsletter : Reisaction - Réseau de l’est de l’île pour les services en anglais (REISA) (2014)
Number of pages: 6

East-Island Network Newsletter : Reisaction - Réseau de l’est de l’île pour les services en anglais (REISA) (2014)
Number of pages: 8

East-Island Network Newsletter : Reisaction - Réseau de l’est de l’île pour les services en anglais (REISA) (2014)
Number of pages: 7

East-Island Network Newsletter : Reisaction - Réseau de l’est de l’île pour les services en anglais (REISA) (2014)
Number of pages: 8

Rapport Annuel : 2013-2014 - Réseau de l’est de l’île pour les services en anglais (REISA) (2014)

Report : Community Network Forum : Enhancing Resiliency to Overcome the Challenges of Work and Personal Stress - Réseau de l’est de l’île pour les services en anglais (REISA) (2013)
A forum on approaches to promoting resilience to turn strengths into strategies to restore abilities to cope and adapt to stress in work and personal situations for ourselves and the communities we serve.

Annual Report : 2012-2013 - Réseau de l’est de l’île pour les services en anglais (REISA) (2013)

East-Island Network Newsletter : Reisaction - Réseau de l’est de l’île pour les services en anglais (REISA) (2013)
Number of pages: 8

East-Island Network Newsletter : Reisaction - Réseau de l’est de l’île pour les services en anglais (REISA) (2013)
Number of pages: 6

Rapport Annuel : 2012-2013 - Réseau de l’est de l’île pour les services en anglais (REISA) (2013)

Annual Report : 2011-2012 - Réseau de l’est de l’île pour les services en anglais (REISA) (2012)

East-Island Network Newsletter : Reisaction - Réseau de l’est de l’île pour les services en anglais (REISA) (2012)
Number of pages: 6

East-Island Network Newsletter : Reisaction - Réseau de l’est de l’île pour les services en anglais (REISA) (2012)
Number of pages: 6

East-Island Network Newsletter : Reisaction - Réseau de l’est de l’île pour les services en anglais (REISA) (2012)
Number of pages: 6

Rapport Annuel : 2011-2012 - Réseau de l’est de l’île pour les services en anglais (REISA) (2012)

Community Network Forum : Addressing Mental Health Issues : An Emerging Challenge for Community Resources - Réseau de l’est de l’île pour les services en anglais (REISA) (2011)
The forum will address the challenges that community resources face as an increasing number of those seeking their services show signs of psychological distress and poor mental health. What is the impact of this emerging clientele on community programs? Where do community resources refer persons in difficulty? How should programs be adapted to address the new challenge? What are the policy and program responses of government and the public health and social services?

East-Island Network Newsletter : Reisaction - Réseau de l’est de l’île pour les services en anglais (REISA) (2011)
Number of pages: 4

East-Island Network Newsletter : Reisaction - Réseau de l’est de l’île pour les services en anglais (REISA) (2011)
Number of pages: 6

East-Island Network Newsletter : Reisaction - Réseau de l’est de l’île pour les services en anglais (REISA) (2010)
Number of pages: 4

East-Island Network Newsletter : Reisaction - Réseau de l’est de l’île pour les services en anglais (REISA) (2010)
Number of pages: 4

East-Island Network Newsletter : Reisaction - Réseau de l’est de l’île pour les services en anglais (REISA) (2010)
Number of pages: 6